Policy decisions matter: Cessation of logging benefits 34 threatened species in Victoria, Australia - Kita R. Ashman; Michelle Ward; Chris R. Dickman; Dan Harley; Leonie Valentine; John Woinarski; Jess R. Marsh; Chris J. Jolly; Don A. Driscoll; Elle Bowd; Darcy J. Watchorn; Nick Clemann; et al. (PLoS ONE, 2025)
In January 2024, the Australian state of Victoria committed to ending native forest logging six years ahead of schedule, a decision that has been advocated for by scientists and conservationists for decades. However, the direct benefits for threatened species from this policy change has not been quantified. This study assesses the spatial overlap between areas approved for logging and the habitats of nationally listed threatened species, to estimate the potential impacts of continued logging and the likely benefits of its cessation. We found that 99% of the areas approved for logging overlapped with the habitats of nationally threatened species. On average, each logging cutblock contained habitat for eight listed species. Areas approved for logging had considerable overlap with the habitat of several threatened species, particularly the Baw Baw frog (Philoria frosti, Critically Endangered, 6.2% of habitat approved for logging), Leadbeater’s possum (Gymnobelideus leadbeateri, Critically Endangered, 6.1%), barred galaxias (Galaxias fuscus, Endangered, 5.6%), Tall astelia (Astelia australiana, Vulnerable, 5.4%), and Colquhoun grevillea (Grevillea celata, Vulnerable, 5%). Notably, these five species are found only in Victoria, thus these values represent the proportion of their entire mapped habitat slated for logging over a short time period. Our findings underscore the need for urgent, nationwide forest protection policies, alongside restoration efforts, to support species recovery and meet global climate and biodiversity commitments.